The Secret Room Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
Biff, Chip, Kipper, Mum, Dad, and Floppy are helping redecorate their new home. While stripping wallpaper, Biff discovers a hidden door in her bedroom. Behind it lies a secret room featuring a miniature replica of their house$1 (Band even tiny versions of themselves and Floppy. The story ends with Biff happily dreaming about her special find.s
This short, funny tale$1 (Btypical of Level 4 stories$1 (Bis designed to support early readers by blending repetition and recognizable characters to reinforce vocabulary and comprehension. Children especially enjoy reading it multiple timess